Real-world clinical evidence of oral semaglutide on metabolic abnormalities in subjects with type 2 diabetes: a multicenter retrospective observational study (the Sapporo-Oral SEMA study) - Sho Furusawa; Hiroshi Nomoto; Chiho Oba-Yamamoto; Jun Takeuchi; Miki Ito; Hiroyoshi Kurihara; Shin Aoki; Aika Miya; Hiraku Kameda; Akinobu Nakamura; Tatsuya Atsumi (Endocrine Journal)
Oral semaglutide has potent anti-hyperglycemic efficacy in phase III trials. However, the complicated dosing instructions hamper to use this drug; therefore, we evaluated the efficacy and safety of oral semaglutide in subjects with type 2 diabetes in a real-world clinical setting. In this multi-center retrospective observational study, we analyzed subjects with type 2 diabetes newly treated with an oral semaglutide for >6 months at four medical centers located in Sapporo, Japan. The changes in glycated hemoglobin, body weight, and other metabolic parameters were evaluated and any adverse event leading to semaglutide discontinuation were recorded from February 2021 to December 2022. This study was registered with the University Hospital Medical Information Network Center (UMIN000050583). Of 543 subjects who met the inclusion criteria, data for 434 subjects (age 55.5 ± 12.6 years; body mass index 29.6 ± 6.0 kg/m2) were analyzed. After a 6 months of observation period, semaglutide 3 mg, 7 mg, or 14 mg was used by 55 (12.7%), 241 (55.5%), and 138 (31.8%) of subjects, respectively. Both glycated hemoglobin and body weight significantly improved: 7.65 ± 1.11% to 6.88 ± 0.91% (p < 0.001) and 80.2 ± 19.2 kg to 77.6 ± 19.2 kg (p < 0.001), respectively. Efficacy was also confirmed in the subgroup switched from other anti-hyperglycemic agents, including dipeptidyl peptidase-4 inhibitors. In total, 154 subjects had symptomatic gastrointestinal symptoms and 39 (7.2%) were discontinued semaglutide due to the adverse events. None of the participants experienced severe hypoglycemic events. Oral semaglutide in subjects with type 2 diabetes improved glycemic control and body weight in a real-world clinical setting.